Performance Evaluation of a PCM-Based Li-Ion Battery Thermal Management System and Proton Exchange Membrane Fuel Cell: A CFD Approach - S, Swathi (My University, 2016)
Effective optimization is crucial for the performance and durability of batteries. Temperature has always been considered a limiting factor of performance in EV batteries. Moreover, it is essential to maintain the thermal conditions to ensure safety and durability. Phase change materials (PCM) are a better method to store thermal energy than conventional thermal management techniques because they do not change temperature when they gain or release energy, effectively enhancing battery efficiency. This study analyses the effect of PCM in a battery thermal management system in a typical 12 A, 14.6 Ah Li-ion battery. Here we have conducted simulations in Ansys Fluent to study the effectiveness of phase change material based thermal management system. The analysis utilizing the NTGK model in Ansys Fluent confirms the superiority of PCM battery thermal management over traditional conventional air-cooled systems. The demand for a better thermal management system in hydrogen fuel cells has increased due to the global trend. Proton exchange membrane fuel cells (PEMFC) are a capable technology for the sustainability of energy evolution. It can offer efficient electricity production from hydrogen and oxygen with zero emissions. The current study focuses on analysing and optimizing four performance parameters of PEMFC: temperature, exchange current density, charge transfer coefficient, and mass flow rate of reactants to enhance performance. PEMFC simulation employs an integrated approach of electrochemical kinetics through Nernst and Butler-Volmer equations with Darcian flow modelling for porous media. PARSIDO solver was utilised to solve current density within the cell. Laminar, Steady state conditions with isotropic material properties and ideal gas behaviour were ensured throughout the simulation. The simulations were done using COMSOL Multiphysics and MATLAB, where the study explored the fluctuations in the performance within the operating temperature range of 50 οC to 80 οC. The accuracy of the results was confirmed by validating it with a PEMFC operated at 160 οC and 0.6 V. Each parameter was evaluated for its power density and current density curves. PEMFC performance was enhanced when the mass transfer coefficient was varied within the theoretical range known, while inlet reactant velocity showed variation in performance within the range of 0.01 m/s to 1.26 m/s. Cathode exchange current density often contributes more to the voltage performance than anode exchange current density. Systematic optimization of these parameters can determine the configurations to improve the current density output, thereby enhancing the applications in the market. This study will also enlighten the thermal management aspects of PEMFC. In a broader aspect, the key findings can support sustainable energy solutions.
Keywords: THERMAL MANAGEMENT; FUEL CELL; CFD APPROACH; Phase change materials (PCM)